A 3D cell culture system for bioengineering human neuromuscular junctions to model ALS - Massih, Bita; Veh, Alexander; Schenke, Maren; Mungwa, Simon; Seeger, Bettina; Selvaraj, Bhuvaneish T.; Chandran, Siddharthan; Reinhardt, Peter; Sterneckert, Jared; Hermann, Andreas; Sendtner, Michael; Lüningschrör, Patrick (Frontiers in Cell and Developmental Biology, 2023)
The signals that coordinate and control movement in vertebrates are transmitted from motoneurons (MNs) to their target muscle cells at neuromuscular junctions (NMJs). Human NMJs display unique structural and physiological features, which make them vulnerable to pathological processes. NMJs are an early target in the pathology of motoneuron diseases. Synaptic dysfunction and synapse elimination precede MN loss suggesting that the NMJ is the starting point of the pathophysiological cascade leading to MN death. Therefore, the study of human MNs in health and disease requires cell culture systems that enable the connection to their target muscle cells for NMJ formation. Here, we present a human neuromuscular co-culture system consisting of induced pluripotent stem cell (iPSC)-derived MNs and 3D skeletal muscle tissue derived from myoblasts. We used self-microfabricated silicone dishes combined with Velcro hooks to support the formation of 3D muscle tissue in a defined extracellular matrix, which enhances NMJ function and maturity. Using a combination of immunohistochemistry, calcium imaging, and pharmacological stimulations, we characterized and confirmed the function of the 3D muscle tissue and the 3D neuromuscular co-cultures. In summary, the human 3D neuromuscular cell culture system presented here recapitulates aspects of human physiology in a controlled in vitro setting.